2014
DOI: 10.1016/j.bbadis.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Oct4 suppresses the metastatic potential of breast cancer cells via Rnd1 downregulation

Abstract: Although Oct4 is known as a critical transcription factor involved in maintaining "stemness", its role in tumor metastasis is still controversial. Herein, we overexpressed and silenced Oct4 expression in two breast cancer cell lines, MDA-MB-231 and 4T1, separately. Our data showed that ectopic overexpression of Oct4 suppressed cell migration and invasion in vitro and the formation of metastatic lung nodules in vivo. Conversely, Oct4 downregulation increased the metastatic potential of breast cancer cells both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…Prominent among these is POU5F1 (better known as OCT4), which has been identified as an essential transcription factor mediating stem-ness. Shen and colleagues studied the effects of overexpression of POU5F1 in MDA-MB-231 and 4T1 breast cancer cell lines, and found that the overexpression of POU5F1 suppressed migration and invasion in these usually aggressive cell types (20).…”
Section: Discussionmentioning
confidence: 99%
“…Prominent among these is POU5F1 (better known as OCT4), which has been identified as an essential transcription factor mediating stem-ness. Shen and colleagues studied the effects of overexpression of POU5F1 in MDA-MB-231 and 4T1 breast cancer cell lines, and found that the overexpression of POU5F1 suppressed migration and invasion in these usually aggressive cell types (20).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a controversial effect of Oct4 was observed in breast cancer. Oct4 was determined to exert a suppressive effect on cell migration and invasion in vitro and the formation of metastatic lung nodules in vivo (28).…”
Section: A B C D Discussionmentioning
confidence: 99%
“…In addition, Oct4 directly regulates CCND1 to promote cell cycle progression and accelerate proliferation and invasion of esophageal carcinoma were provided in previous report [36]. In contrast, other reports have found that downregulation of Oct4 in breast cancer cell lines induce epithelial-tomesenchymal transition (EMT) and lead to increased migration, invasion and metastasis to the lung by regulating Rnd1 [37,38]. These contradictory results suggest that different expression levels of Oct4 impart different oncogenic abilities according to state of cancer progression.…”
Section: Discussionmentioning
confidence: 96%